Undergraduate perceptions of value: degree skills and career skills - Galloway, Kyle W. (Royal Society of Chemistry, 2017)
Recent data suggests that of the UK students graduating with a degree in chemistry in 2015, only 18.9% continued to employment as ‘Science Professionals’. While this shows the wide range of employment that is available for chemistry graduates, it also highlights the need for them to have relevant transferable skills, rather than just the well-developed, subject-specific knowledge that they would be expected to possess. In 2010 Hanson and Overton published a study on the degree skills valued by UK graduates who had found employment and then reflected on the most useful aspects of the degree course. The new investigation reported here expands on this previous work by evaluating the perceived value of these skills by chemistry undergraduate students (years 1, 2, 3) along with their planned occupation after graduation. The results of the skills questionnaire are discussed, along with a survey of the main skills that the students wished to gain by participating in a new extra-curricular module specifically designed to enhance career skills, and the activities designed to develop those skills.